Be Pouya! (Metaphor for Iranian Clients During Pandemic COVID-19) - Bonnie Bozorg (Journal of Social Behavior and Community Health)
Dear Editor in Chief The results of several studies in general show that metaphors may play an important role in facilitating the processes of treatment in counseling and psychotherapy (Muran et al., 1990). They also reveal that metaphor therapy is a creative method that uses its imaginative power to achieve the goal easier. Humans talk to each other in different ways about their experiences, feelings and thoughts. One of these methods is to use metaphor (Pritzker, 2003). According to Lakoff, people mostly use metaphors when talking about abstract concepts. In their view, metaphor is not a decorative thing or specific to literature, but flows in the daily thought and action of human beings and shows the structure of individual thought (Lakoff, 1993). In the pandemic Coronavirus Disease 2019 (COVID-19), where social isolation has increased, depressed mood is obvious (Ahmed, 2020). Depression that affects by COVID-19 is an emotional response that is because of emotion dysregulation and negative social behaviors (Leaune, 2020). Social distancing causes loneliness that is related to maladaptive behaviors and poor quality of life (Ali & Green, 2019). In system theory, there is a link between the belief that depressed mood selectively increases the possibility of access to negative concepts and interpretive structures, that is, depressed mood prepares the trigger for these negative structures so that they can be used for interpretation and experiences (Teasdale, 1993). In clinical psychology, interest in metaphor focuses on its role in communication processes and cognitive flexibility in psychotherapy (Tay, 2018). The central identity of creative arts therapies lies in the commitment to create and manipulate metaphor as a mediator in treatment. It is better to challenge with clients to be creator (Zhang, 2020). During online treatment in pandemic period, my clients use many metaphors to better understand the concept and process of it. One of the steps in treatment is sequencing goals. One of my clients named it “Pouya steps” as a metaphor. He imagines a person named ‘Pouya’ play an important role in accompanying him in this way. When I checked the background logic of using this word, I realized due to meaning of ‘Pouya’ in Persian (means active and ongoing) it was used as his imaginary role to stimulate positive emotion for doing his goal. Flexible and active thinking will help the process of changing. After that word called’ Pouya” was one metaphor that usually is used in therapy. Pouya is not imagery role for me. He is actual man and virtual (my husband) that his name is also a metaphor for me when I feel sad, helplessness, hopelessness and frustration. Being like his name and him, active and non-stopping. He plays an important role in behavior activation and coping with misbehavior such as social isolation. In summary, I just give one example but there are so many that could not be rejected. it’s important to be aware of their metaphor and its role in successful treatment. Metaphor helps us to understand something unknown from the perspective of something familiar. The seed of a new idea is created in the mind and helps to flourish the latent ideas. This key topic provides new possibilities for "insight" and therapy. Useful metaphors such as ‘Pouya’ play an important role in facilitating the processes of change in counseling and psychotherapy.